Pengaruh Entrepreneurial Education, Entrepreneurial Self-Efficacy, Dan Entrepreneurial Attitude Terhadap Entrepreneurial Mindset Mahasiswa Administrasi Bisnis Telkom University - Arditia, Al-Fath Duta; Hidayat, Agus Maolana (eProceedings of Management, 2024)
The current state of entrepreneurship in Indonesia is far from ideal. Out of a population of 260 million,Indonesia has a total of 8.06 million national entrepreneurs. (Ministry of Industry, 2018) in other words, the ratio of entrepreneurs in Indonesia is around 3.1% of the total population.of entrepreneurs in Indonesia is around 3.1% of the total population. The majority of business owners in Indonesia are graduates ofhigh school (SMA) or around 39%. This naturally raises a series of questions about the role of education, especially higher education, which specificallyof education, especially universities that specifically educate and give birth to prospective entrepreneurs in the future.in the future. In some developing countries including Indonesia, entrepreneurial mindset is influenced by factors such as Entrepreneurial Educationis influenced by factors such as Entrepreneurial Education, Entrepreneurial Attitude, and Entrepreneurial SelfEfficacy, in preparing students for success in the world of entrepreneurship. This research is aquantitative research with experimental methods, with a known population of 1847 active students in the year 2023 at the moment, and a total population of 1847 active students in the year 2023 at the moment.year 2023 at this time, and comes from Telkom University students who have taken Business Administration from semester 1 to semester 7.The results of this study revealed that Entrepreneurial Education,Entrepreneurial Self-Efficacy and Entrepreneurial Attitude simultaneously contributed significantly to thethe formation of Entrepreneurial Mindset.Keywords-entrepreneurship, self effiracy, mindset, attitude